Exploring teacher readiness to integrate information and communication technologies into the teaching and learning process: a case study of two Gauteng schools - Naicker, Tinika (My University, 2017)
The Department of Education (2004) stipulated in the White Paper on e-Education policy document that all teachers (including Gauteng teachers) were to be Information and Communication Technology (ICT) capable by the year 2013. This research study was targeted at exploring how ready the teachers from the researched schools were to integrate ICTs into the teaching and learning process. In exploring teachers’ readiness, the study focused upon four areas, namely teachers’ ICT knowledge (informed by Mishra and Koehler’s (2006) TPACK model), teachers’ ICT attitudes (informed by Parasuraman’s (2000) TRI), the ICT training received, and the role played by school principals in contributing to teachers’ ICT readiness. By exploring these areas information was obtained on how teachers were prepared and whether they were prepared, which gave insight into how ready they were for the ICT integration process. In order to gain the relevant data, ten teachers from two Gauteng schools were interviewed and administered a questionnaire to complete. In addition, the school principal from each school was interviewed. It was found that the majority of the research participants had a positive attitude towards the integration of ICTs into teaching and learning. These teachers also had a good leadership influence, which provided support and conditions that were also essential in facilitating the ICT integration process. However, it was found that the training that majority of the teachers received was not instrumental in providing them with the required ICT knowledge. Consequently, based on these two areas (ICT knowledge and ICT training) serving to be problematic, it is concluded that the teachers at the researched schools were not adequately prepared and thus predominately not ready to integrate ICTs effectively into the teaching and learning process in their schools. The findings of the study, the literature reviewed, and the theoretical foundations central to this study were used to develop a teacher ICT preparation framework. This framework was developed to inform the preparation that teachers receive for the ICT integration process. The framework could contribute to teachers being more ready to integrate ICTs effectively into the teaching and learning process in their schools.
A research report submitted to the School of Education, Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Education. August 2017
Keywords: Educational technology--South Africa; Education--Computer-assisted instruction; Teachers--South Africa